Ecological niche modeling of invasive alien plant species in a protected landscape - G.C.B. Paclibar; E.R. Tadiosa (Global Journal of Environmental Science and Management)
Non-native plants that can cause adverse effects are otherwise known as invasive alien plant species which pose a major threat to plant biodiversity conservation and sustainability. This study is dedicated to determine the plant diversity and to assess the vulnerability of Quezon Protected Landscape, Southern Luzon, the Philippines to invasive alien plant species. Data from 90 10x10 m randomly established plots using the quadrat method showed that there are 318 plant species wherein 208 are native, 100 are non-native, and 10 are invasive. Results from the association of the physicochemical factors and the presence of invasive alien plant species through Spearman rho test revealed that most of the physicochemical factors have significant association except percent slope and hill shade. Soil pH, aspect and number of non-native plants show positive association while soil moisture, leaf litter thickness, elevation, species richness, species evenness, plot species diversity index, and the number of native plants signify negative association. Differences between the plots of with and without invasive alien plant species in physicochemical factors indicate that most of the physicochemical factors have a significant difference between plots of with and without invasive alien plant species except percent slope, hill shade, and aspect. Lastly, the MaxEnt model exemplifies that the most suitable predicted conditions for invasive alien plant species are at the edges of boundary and buffer zones. This study implies that most of the physicochemical factors are linked to the presence of invasive alien plant species and Quezon Protected Landscape has a low vulnerability to invasive alien plant species invasion.